2013
DOI: 10.1007/s00520-013-1970-9
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a prognostic scale for hospitalized patients with terminally ill cancer in China

Abstract: We identified eight indicators predictive of poor survival in Chinese patients hospitalized with terminal cancer. A prognostic scale that includes these indicators may help in making decisions about end-of-life care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…In palliative care teams, worse pain was associated with longer survival, whereas the opposite was observed in hospice. Most previous studies in patients referred to specialized palliative care did not find a significant association between pain and survival, 1,[25][26][27][28]30,31,[33][34][35]37,[44][45][46][47][49][50][51][52][53][54][55] but one study in patients with advanced cancer with short life expectancy (2-9 month) found worse pain to be associated with shorter survival time, 43 similar to our finding in hospice patients. The unexpected association between worse pain and longer survival in palliative care teams found in this study might be explained in the same way as with emotional function, that is, by early referral to specialized palliative care for pain control.…”
Section: What This Study Addssupporting
confidence: 88%
See 3 more Smart Citations
“…In palliative care teams, worse pain was associated with longer survival, whereas the opposite was observed in hospice. Most previous studies in patients referred to specialized palliative care did not find a significant association between pain and survival, 1,[25][26][27][28]30,31,[33][34][35]37,[44][45][46][47][49][50][51][52][53][54][55] but one study in patients with advanced cancer with short life expectancy (2-9 month) found worse pain to be associated with shorter survival time, 43 similar to our finding in hospice patients. The unexpected association between worse pain and longer survival in palliative care teams found in this study might be explained in the same way as with emotional function, that is, by early referral to specialized palliative care for pain control.…”
Section: What This Study Addssupporting
confidence: 88%
“…This is in accordance with three systematic reviews on survival prediction in cancer patients with expected survival of ⩽ 90 days. [16][17][18] Several previous studies of patients referred to specialized palliative care also found low physical function (activity of daily living, usual activities, mobility, performance score, self-care, physical function, or physical wellbeing), 1,[26][27][28]30,31,35,37,[42][43][44][45][46] problems related to eating/low or reduced weight (reduced appetite, early satiety, eating problems, dysphagia, and cachexia), 1,[25][26][27][28]30,31,[33][34][35][36][37][43][44][45]47,48 dyspnea, 1,26,28,31,[33][34][35]37,43,45,46,[48][49][50]…”
Section: What This Study Addsmentioning
confidence: 95%
See 2 more Smart Citations
“…Regarding countries, the following stands out Australia (10%), Canada (12%), South Korea (10%), United States (10%), Netherlands (8%), and Taiwan About the definitions: "end-of-life" was characterized in five studies, four quantitative and one qualitative; "palliative care" was defined in 15 studies, 11 quantitative and four qualitative and "terminally ill" appeared in 35 studies, 31 quantitative and five qualitative. (Appendix 1) (5,8,9,15,16,17,18,19,3,20,21,22,23,24,25,26,27,28,29,30,11,12,10,13,14,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,5...…”
Section: Literature Searchmentioning
confidence: 99%